Measures of Injury Severity and Prediction of Acute Traumatic Brain Injury Outcomes. Issue 2 (March 2015) - Perrin, Paul B.; Niemeier, Janet P.; Mougeot, Jean-Luc; Vannoy, Charles H.; Hirsch, Mark A.; Watts, John A.; Rossman, Whitney; Grafton, Lori M.; Guerrier, Tami D.; Pershad, Rashmi; Kingsbury, Carla A.; Bartel, Sheri W.; et al.
Abstract : Objective: To examine the comparative efficacy of 3 common measures of traumatic brain injury (TBI) severity for predicting inpatient outcomes upon hospital discharge. Setting: Acute brain injury rehabilitation unit at level 1 trauma center. Participants: 100 patients with TBI. Design: Retrospective analysis of injury severity, demographic, and outcome data. Main Measures: Glasgow Coma Scale (GCS) at admission, time to follow commands (TTC), duration of posttraumatic amnesia (PTA), and Functional Independence Measure at hospital discharge. Results: A hierarchal multiple regression revealed that duration of PTA was a significant and powerful unique predictor of Functional Independence Measure scores at discharge (β = −0.46, P = .001), while TTC (β = 0.26, P = .056) and GCS (β = 0.16, P = .143) were not. These effects were present even after controlling for age, gender, educational level, racial/ethnic minority status, cause of injury, history of substance abuse, and neurosurgical intervention. Conclusion: Although clinicians often use GCS scores and TTC when assessing acute TBI severity and during treatment formulation, this study provides evidence that duration of PTA may be a more meaningful predictor of patients' functional levels at discharge.